In Control of Legality Business in the Republic of Uzbekistan Role of the Ombudsman - Alisher Nasirdinovich Juraev (Global Scientific Publishing, 2023)
the main goal of this article is to create conditions for protecting the rights of business entities using various means. At the same time, the world experience of protecting the rights of business entities under the President was studied and its impact on promoting business was analyzed. In particular, the reforms of the last 3-4 years were considered and the state developed strategic programs. A representative institution of entrepreneurs was created . The goals and objectives of the Representative Institute are analyzed . Areas of activity were studied
Keywords: subjects of entrepreneurship; protection; institution of representation